Perkembangan Reksadana Syariah di Indonesia - Istikomah Dwi Lestari; Metti Rahma Saniagi; Fani Alviyanto; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. Investment can simply be defined as an activity of investing capital or assets with the aim of making a profit. More practically, investment is a commitment of a certain amount of funds or other resources made now with the hope of gaining profits in the future. The aim of this research is to find out about the development of sharia mutual funds in Indonesia. The method used in this research is a bibliographic approach sourced from books and scientific journals according to the topic and focus of the research. The results of this research show that the development of sharia mutual funds in Indonesia has been quite significant with the number of sharia mutual funds increasing and many investors already using sharia mutual funds as their investment instruments. Keywords: Sharia Mutual Funds, Investment, Islam.